Human rights as human independence a philosophical and legal interpretation - Montero, Julio (Pennsylvania studies in human rights, 2022)
"Human Rights as Human Independence offers a comprehensive, systematic, and complete account of the nature, content, and scope of human rights to be used to interpret international documents and make informed decisions about how human rights practice must continue in the years to come"--